The Existence of Al-Jarh Wa Al-Ta'dil (In Modern Hadith Studies) - Andi Muhamad Hidayat; Tajul Arifin; Muhamad Chaedar Rafiq (al-Afkar, Journal For Islamic Studies, 2025)
The phenomenon of slander that occurs among Muslims, the validity and existence of hadiths are tarnished is marked by the existence of Maudhu hadiths which are spread by irresponsible transmitters. To ensure the authenticity of the hadith, there is a need for a means of criticism of the matan and sanad, including the transmitter. So this research attempts to present the history of the development of hadith sanad criticism from the perspective of jarḥ and ta'dīl using a historical approach method. Therefore, this research is part of qualitative research. From this research, a result was obtained; Firstly, that the critical study of hadith has basically been practiced since the lifetime of the Prophet SAW, although aspects of the sanad or personal rāwi (jarḥ and ta'dīl) and this study continued to develop in subsequent periods. Second, in reality, currently the existence of false hadiths continues to spread and develop and even false hadiths appear that have not been studied and researched by previous scholars, so the need for jarḥ and ta'dīl studies to determine the authenticity of hadiths continues at all times and does not become stagnant with changing times.